Hambatan dan Peluang dalam Penerapan Media Pembelajaran Berbasis Augmented Reality di Sekolah Dasar: Tinjauan Sistematis Praktik Pendidikan - Nisa, Rofiatun (Universitas Islam Negeri Raden Fatah Palembang, 2025)
The rapid advancement of educational technology has opened opportunities for integrating innovative tools such as Augmented Reality into elementary education. This systematic literature review investigates the barriers and opportunities in applying Augmented Reality-based learning media in elementary schools. Following the PRISMA protocol, 35 articles published between 2015 and 2024 were analyzed to identify technological, infrastructural, pedagogical, and teacher competency challenges. Key barriers include hardware and software limitations, insufficient technical support, and lack of teacher training. However, significant opportunities exist, such as enhanced interactivity, project-based learning facilitation, and skill development for 21st-century competencies. The study emphasizes the importance of collaborative efforts among policymakers, educators, and technology providers to address these challenges. Future research should evaluate Augmented Reality's long-term impact on educational outcomes and develop cost-effective solutions to bridge access disparities. This review fosters an inclusive and adaptive education system aligned with technological advancements.